SOMATIC OPTIMIZATION FOR INFANTS WITH PERINATAL CENTRAL NERVOUS SYSTEM INJURY IN THE FIRST YEAR OF LIFE - Abdullaeva Muslima Akhatovna; Urokova Vazira Khamidovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Relevance of the Problem: The issue of perinatal post-hypoxic brain injury is extremely relevant, as it is associated with the increasing incidence of brain diseases in newborns and plays a leading role in the development of childhood disabilities. Significant challenges remain in diagnosing and treating this condition, even in the absence of gross neurological pathology, affecting the subsequent neuropsychological and somatic development of children. It is known that the neurological condition of newborns with perinatal post-hypoxic brain injury largely depends on the brain's maturity, the severity of the injury, and associated diseases. However, clinical signs do not always reflect the true severity and extent of central nervous system damage, which may be influenced by the high neuroplastic potential of an infant's brain in the first year of life. The disease outcome, including adverse results, becomes apparent only at 9-12 months of age. Currently, therapeutic measures for infants with perinatal post-hypoxic central nervous system injury are sometimes insufficiently effective, highlighting the importance of developing optimal methods to influence the restoration of damaged brain tissues. It is crucial to minimize the source of damage and preserve as many functioning nerve cells as possible, especially for infants expected to exhibit continued neurological symptoms by the end of the first year of life.